The Implementation of Project-Based Learning and Discovery Learning Models on Students’ Writing Narrative of SMA Swabina Karya Medan - Sayumen Manao; Sondang Manik; Lastri W Manurung; Erika Sinambela (South Sulawesi Education Development (SSED), 2024)
The study dealt with the implementation of project-based learning(PjBL Model) and discovery learning (DL Model) on students’ writing narrative of SMA Swabina Karya Medan. It is aimed to describe the students’ writing narrative ability before taught by PjBL and DL models, to show the students’ writing narrative ability after taught by PjBL and DL models, to find out the differences effect of the implication between PjBL and DL models on the students’ writing narrative ability. This study was quasi experimental research. It was be carried out with 2 classes which was treated such as the experimental class- 1 and experimental class-2 which was given test; pre-test and post-test at the same time. Writing narrative test was a data. The result of the study found that the students’ writing narrative ability before implemented by PjBL and DL models showed lower. It proved that in experimental class-1, 31 (88.57%) students was not got categorized fail and in experimental class-2, 29 (82.86%) students was categorized fail. The students’ writing narrative ability after implemented by PjBL and DL models showed higher. It proved that in experimental class-1, all the students or 100% students was categorized pass and in experimental class-2, 19 (54.29 %) students was categorized pass. There was found a differences effect of the implementation PjBL and DL models on the students’ writing narrative ability. It proved from the result of Wilcoxon test showed -5.174 < -5.169. It means H0 was accepted.